2014
DOI: 10.5897/ijbc2013.0670
|View full text |Cite
|
Sign up to set email alerts
|

Farmers dependency on forests for nutrients transfer to farmlands in mid-hills and high mountain regions in Nepal (case studies in Hemja, Kaski, Lete and Kunjo, Mustang district)

Abstract: The study assessed NPK (Nitrogen, Phosphorus, Potassium) transferred through litter from forest to farmlands, forest product extraction systems and farmers' perceptions on forest dependency for maintaining farm fertility in Lete and Kunjo, Mustang (high mountain) and Tibrekot, Kaski (mid-hill region), Nepal. NPK in composite samples of forest litter were determined by standard methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Agriculture in Nepal is still largely subsistence in nature and dominated by smallholder farmers and mixed cropping systems. Many studies have shown that a decline in soil fertility across the country is a key factor that constrains the productivity of most crops and farming systems (Balla et al 2014;Rijal 2001;Schreier, Brown, and Shah 1995). There are a variety of other causes that are responsible for the stagnant productivity; for example, climatic variations (Panday 2012), changing farming practices (Ghimire and Panday 2017;Paudel et al 2014), and soil erosion (Maharjan and Joshi 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture in Nepal is still largely subsistence in nature and dominated by smallholder farmers and mixed cropping systems. Many studies have shown that a decline in soil fertility across the country is a key factor that constrains the productivity of most crops and farming systems (Balla et al 2014;Rijal 2001;Schreier, Brown, and Shah 1995). There are a variety of other causes that are responsible for the stagnant productivity; for example, climatic variations (Panday 2012), changing farming practices (Ghimire and Panday 2017;Paudel et al 2014), and soil erosion (Maharjan and Joshi 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Rasul & Thapa, (2004) reported that to enhance the soil"s biological fertility, promotion of leguminous crop cultivation, agroforestry and livestock farming are good approaches. Bajracharya, & Sherchan, (2009) ;Balla et al, (2014) described that mountain farmers of Nepal are heavily dependent on forest based farming system to sustain their livelihoods. As most of them have no alternatives except the natural resource base to fulfill their subsistence requirements such as food, fodder, fuel wood, fiber, construction materials and other non-wood forest products.…”
Section: Introductionmentioning
confidence: 99%
“…In our case also, contribution of both practices seems supportive in conserving forest situated nearby local village. e farmers are utilizing their farmland for forest-based products required for their household, but still they depend on surrounding forest to fulfill the deficit demand [6,25]. e improved practitioners are fulfilling their maximum portion of demand (90% fodder, 92% fuelwood, and 67% leaf litter) from their farmland.…”
Section: Contribution Of Agroforestry Practice On Forestmentioning
confidence: 99%
“…ough efforts are being made for the promotion of agroforestry practices, there is still a huge gap in identifying better agroforestry practice. Nevertheless, some studies on agroforestry have been conducted in Nepal such as contribution on households' economy [23], livelihood enhancement and food security [24], and satisfying households' requirements [25,26]. e studies conducted so far seemed insufficient to provide substantial backup to appraise better agroforestry practices.…”
Section: Introductionmentioning
confidence: 99%